CaMKII as a therapeutic target in catecholaminergic polymorphic ventricular tachycardia type 1. (24th May 2021) - Sadredini, M; Manotheepan, R; Haugsten Hansen, M; Frisk, M; Louch, WE; Lehnart, SE; Anderson, ME; Sjaastad, I; Stokke, MK
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): South-Eastern Norway Regional Health Authority Background: In catecholaminergic polymorphic ventricular tachycardia type 1 (CPVT1) adrenergic activation of the cardiac ryanodine receptor (RyR2) causes spontaneous calcium release and triggers arrhythmias. Calcium/calmodulin-dependent protein kinase II (CaMKII) can contribute to such arrhythmogenic calcium release and has been proposed as a therapeutic target in CPVT1. To predict the efficacy and safety of this strategy, it is necessary to know whether the mechanism for CaMKII activation is important for its arrhythmogenic effects, and if inhibition has proarrhythmic effects. We tested (1) if oxidation of CaMKII contributes to spontaneous calcium release in CPVT1 and (2) if inhibition of CaMKII in this condition can induce calcium alternans. Methods: Mice with the CPVT1-causative mutation RyR2-R2474S (RyR2-RS) were crossed with mice with the CaMKII M281/282V (MMVV) mutation that prevents CaMKII M281/282 oxidation, to create double mutants (RyR2-RSxMMVV). Telemetric ECG surveillance was used to study in vivo arrhythmias following an adrenergic challenge by i.p. administration of the beta-adrenoceptor agonist isoprenaline. Confocal line-scan imaging and whole-cell calcium imaging were used to study arrhythmogenic calcium release in isolated left ventricular cardiomyocytes during stimulation with isoprenaline. Results: As expected, RyR2-RS mice exhibited more arrhythmic events and spontaneous calcium release (i.e. calcium sparks and calcium waves) compared to wild-type mice. Treatment of RyR2-RS cardiomyocytes with either the CaMKII inhibitor KN-93 or the antioxidant n-acetyl-cysteine reduced spontaneous calcium release (i.e. calcium sparks and calcium waves, for KN-93 and n-acetyl-cysteine, respectively). Interestingly, CaMKII inhibition by KN-93 also increased both incidence and degree of arrhythmogenic calcium alternans in RyR2-RS cardiomyocytes. This adverse effect was a result of prolonged refractoriness of calcium release. Furthermore, to test whether the protective effect of antioxidant treatment in RyR2-RS was mediated via CaMKII oxidation, we compared arrhythmias and spontaneous calcium release (i.e. calcium waves) in RyR2-RSxMMVV with RyR2-RS. However, these two genotypes did not differ in either incidence or severity of arrhythmias, and showed similar degree of spontaneous calcium release. Conclusions: Inhibition of CaMKII protects against spontaneous calcium release in CPVT1, and is a promising therapeutic strategy. However, the fact that such inhibition also induces calcium alternans needs further exploration. Antioxidative agents also attenuate arrhythmogenic calcium release in CPVT1 cardiomyocytes, but this effect does not seem to involve the M281/282 CaMKII oxidation site. Future studies should explore other oxidation sites.